Frequent detection of IFN-gamma -producing memory effector and effector T cells in patients with progressive multifocal leukoencephalopathy - de Goër de Herve, Marie-Ghislaine; Dekeyser, Manon; Hendel-Chavez, Houria; Maillart, Elisabeth; Labeyrie, Céline; Adams, David; Moreau, Thibault; Lubetzki, Catherine; Papeix, Caroline; Stankoff, Bruno; Gasnault, Jacques; Taoufik, Yassine (Frontiers in Immunology, 2024)
Progressive Multifocal Leukoencephalopathy (PML) is a rare and deadly demyelinating disease caused by JC virus (JCV) replication in the central nervous system. PML occurs exclusively in patients with severe underlying immune deficiencies, including AIDS and hematological malignancies. PML has also emerged as a significant threat to patients on potent new immunosuppressive biologics, including natalizumab in multiple sclerosis. Here, we developed an IFN-γ release assay (IGRA) that mainly detects JCV-specific effector memory T cells and effectors T cells in the blood. This assay was frequently positive in patients with active PML (with a positive JCV PCR in CSF) of various underlying immunosuppression causes (84% sensitivity). Only 3% of healthy donors had a positive response (97% specificity). The frequency of positivity also increased in multiple sclerosis patients according to the time on natalizumab (up to 36% in patients treated for more than 48 months, who are considered at a higher risk of PML).The results show this assay's frequent or increased positivity in patients with PML or an increased risk of PML, respectively. The assay may help to stratify the risk of PML.